Facile synthesis of Ge1−xSnx nanowires. (5th June 2020) - Xu, Ying; Al-Salim, Najeh; Lim, Teck Hock; Bumby, Chris W; Cheong, Soshan; Tilley, Richard D
Abstract: We report a facile one-pot solution phase synthesis of one-dimensional Ge1− x Sn x nanowires. These nanowires were synthesized in situ via a solution-liquid-solid (SLS) approach in which triphenylchlorogermane was reduced by sodium borohydride in the presence of tin nanoparticle seeds. Straight Ge1− x Sn x nanowires were obtained with an average diameter of 60 ± 20 nm and an approximate aspect ratio of 100. Energy-dispersive x-ray spectroscopy (EDX) and powder x-ray diffraction (PXRD) analysis revealed that tin was homogeneously incorporated within the germanium lattices at levels up to 10 at%, resulting in a measured lattice constant of 0.5742 nm. The crystal structure and growth orientation of the nanowires were investigated using high-resolution transmission electron microscopy (HRTEM). The nanowires adopted a face-centred-cubic structure with individual wires exhibiting growth along either the ⟨111⟩, ⟨110⟩ or ⟨112⟩ directions, in common with other group IV nanowires. Growth in the ⟨112⟩ direction was found to be accompanied by longitudinal planar twin defects.